STUDI KOMPARASI PROYEKSI HARGA CABAI RAWIT DI PULAU SUMATERA VS PULAU JAWA - Muhammad Faisal Akbar (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2022)
The agricultural sector is a sector that plays an important role in the national economy. Indonesia has determined several potential superior commodities based on economic value and high market demand. Several horticultural commodities that have been designated as leading commodities by Indonesia are various chilies, shallots and oranges. This study intends to conduct a study on the projection (forecasting) of cayenne pepper prices on the island of Sumatra and Java island using a time-series analysis approach. Time-series data has advantages in terms of analysis and projection so that researchers can provide an overview of the price behavior of cayenne pepper in the market. The method used in analyzing projections is using Trend Analysis (Linear), Moving Average, and Polynomial methods. The final results from the Trend Analysis (Linear), Moving Average, and Polynomial methods, which have superior results if you look at the results of R Squared, are Java. Descriptive analysis results seen from the average (mean), standard deviation, drinking value and maximum, which is superior is the island of Sumatra.